Subdividing the commons: the politics of property rights transformation in Kenya’s Maasailand - Mwangi, Esther (International Food Policy Research Institute, 2006)
This paper discusses the internal processes and decisions that characterized the transition from collectively held group ranches to individualized property systems among the Maasai pastoralists of Kajiado district in Kenya. It addresses the question of why group ranch members would demand individualized property systems, but then turn against the outcome. In addressing this puzzle the paper discusses the process of land allocation and distribution during group ranch subdivision. It examines who the main actors were during subdivision, their degree of latitude in crafting and changing rules, and the interactions between Maasai and state institutions. Findings suggest that, because the process by which property rights change is so intertwined with politics, we may need to move beyond economic models of relative price changes and state enforcement in order to better understand such transitions. Models that accommodate competition by actors and the possibility that state actors may not provide the arbitration or enforcement that is often taken for granted are more useful for analyzing the complexities of shifting property rights. When the possibility for conflict and competition is factored into the property rights equation, the relative gains from privatizing/individualizing may not be as large or as obvious as anticipated.